ANALISIS KANDUNGAN LOGAM MERKURI, KADMIUM, TIMBAL DAN SIANIDA PADA ALIRAN SUNGAI INDRAGIRI, KABUPATEN INDRAGIRI HULU - Nola Oktaria; Tengku Abu Hanifah; Sofia Anita (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Increasing activities of illegal gold mining caused environmental damage of the river. Heavy metal pollution of Hg, Pb, Cd and CN‾ were derived from mining waste dumped into the river. This research was analysed of the metal content of Hg, Pb, Cd and CN‾. Samples were taken at 4 sampling points, for Hg, Pb and Cd were analyzed by Atomic Absorption Spectrophotometry method and CN‾ were analyzed by Uv-Vis Spectrophotometry. The results show that the concentration of Hg was in between 1.30 – 3.35 ppb, Cd 0.1002 – 0.1684 ppm, Pb not detection – 0.988 and CN¯ not detection – 0.72 ppm. All of the metal concentration have passed a specified threshold limit of PP No. 82 Tahun 2001, except for Pb on the ST2 and Cyanide ion on the ST4, that are still below the limit.